Portofolio Mean Variance Efficient Dua Konstrain Pada 15 Saham Indeks LQ45 - Fariz Rivalno; Dewi Murni; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Portfolio is an investment tool in stocks that divide capital into a number of stocks according to the weight or percentage determined by the investor. For that, investors need to establish an optimal portfolio. One of the optimal portfolio methods is Mean Variance Efficient Two Constraints Portfolio. The purpose of this study is to obtain a formula for determining the investment weight and its application onMean Variance Efficient Two Constraints Portfolio to obtain minimal investment risk from 15 LQ45 Index stocks. The type of this research is applied research. The type of data is secondary data, in the form of closing pricestocks on the LQ45 Index period of November 9th, 2016 - March 2nd, 2017. Steps in the establishment of a portfolio is calculate the return, average return, variance return, covariance return, and find weight investment through formula on the portfolio. The result of this research is obtained a formula for determining the investment weight on Mean Variance Efficient Two Constraints Portfolio and formed an optimal portfolio on 15 LQ45 Index stocks. The portfolio provides 0.07% average return and 0.01% risk. Keywords –Constraint, LQ45 Index, Portfolio, Return, Stocks